Expression of a multigene mushroom luciferin biosynthesis pathway as a pseudo-polycistron in plants - Samson, David; Thompson, Natalie S.; Sheri, Vijay R.; Rudrabhatla, Sairam V.; Curtis, Wayne R. (Scientific reports, 2025)
Mushroom bioluminescence is based on a luciferin/luciferase cycle that includes four catalytic enzymes and a post-translational modifier phosphopantetheinyl-transferase (NpgA). The luciferin cycle includes conversion of the plant cell wall precursor caffeic acid to the mushroom luciferin (3-hydroxyhispidin) substrate—suggesting a logical system for development of in vivo luciferin production rather than addition of exogenous luciferin substrate. In planta luciferin biosynthesis is demonstrated from a polycistronic concatenation of the luciferin pathway genes with intervening self-cleaving intein-F2A peptides. Bioluminescence was greater with NpgA transiently expressed separately from the luciferin biosynthesis (LBS) polycistron in N. benthamiana but was not detectable in tomato even with all genes on separate promoters. Separation of the bioluminescence reporter and luciferin substrate pathway facilitated studies of mushroom luciferase that reveal instability for the luciferin substrate. Agrobacterium expressing the luciferase is shown to be an effective quantitative biosensor for both the presence of luciferin as well as plant tissue quenching of bioluminescence during tissue disruption. Large plant species-dependent differences in bioluminescence assay quenching are observed, with tomato displaying instantaneous suppression comparable to wild-type negative controls. Although bioluminescence is observed using transient luciferin/luciferase co-expression in tobacco ( N. benthamiana ), luciferin could not be isolated for use in exogenous assay. The challenge of using the mushroom luciferin biosynthesis pathway in transgenic plants as a complementation reporter is discussed in the context of our inability to detect luciferin in tomato transgenic lines after homozygous segregation using digital PCR. The utilization of in vivo mushroom luciferin biosynthesis is anticipated to be increasingly effective in the future based on ongoing gene improvements in pathway biosynthesis subject to the constraint of substrate instability.